Do estimates of contemporary effective population size tell us what we want to know?. Issue 8 (26th April 2019) - Ryman, Nils; Laikre, Linda; Hössjer, Ola
Abstract: Estimation of effective population size ( N e ) from genetic marker data is a major focus for biodiversity conservation because it is essential to know at what rates inbreeding is increasing and additive genetic variation is lost. But are these the rates assessed when applying commonly used N e estimation techniques? Here we use recently developed analytical tools and demonstrate that in the case of substructured populations the answer is no. This is because the following: Genetic change can be quantified in several ways reflecting different types of N e such as inbreeding ( N eI ), variance ( N eV ), additive genetic variance ( N eAV ), linkage disequilibrium equilibrium ( N eLD ), eigenvalue ( N eE ) and coalescence ( N eCo ) effective size. They are all the same for an isolated population of constant size, but the realized values of these effective sizes can differ dramatically in populations under migration. Commonly applied N e ‐estimators target N eV or N eLD of individual subpopulations. While such estimates are safe proxies for the rates of inbreeding and loss of additive genetic variation under isolation, we show that they are poor indicators of these rates in populations affected by migration. In fact, both the local and global inbreeding ( N eI ) and additive genetic variance ( N eAV ) effective sizes are consistently underestimated in a subdivided population. This is serious because these are the effective sizes that are relevant to the widely accepted 50/500 rule for short and long term genetic conservation.  The bias can be infinitely large and is due to inappropriate parameters being estimated when applying theory for isolated populations to subdivided ones.